ARTISTIC EDUCATION IN CUBA. ANTECEDENTS AND PRESENT STATE - Sánchez Ortega, Paula M. (Atenas, 2013)
This monography offers a panoramic view on Cuban artistic education. Fundamental facts and events of different artistic manifestations within the general education are characterized, having into account the happenings of specialized artistic education and those artistic events that have influenced in aesthetic and artistic education of the general population. It starts by the development of painting and its evolution up to plastic education, then it follows with Musical education from the colonial period to nowadays. In accordance with these topics, it also deals with the evolution of the training of teachers, with emphasis on the period after the triumph of the Revolution in 1959, since this is the initiating stage for the training of professionals in charge of leading the different manifestations of artistic education in Cuba.